2020
DOI: 10.1111/anu.13190
|View full text |Cite
|
Sign up to set email alerts
|

Addition of enzyme‐digested hydrolysed porcine mucosa to low‐fishmeal feed improves growth, intestinal microbiota, and intestinal peptide and amino acid transporter expressions in hybrid groupers ( Epinephelus fuscoguttatus ♀ ×  E. lanceolatus ♂)

Abstract: In this study, five iso-nitrogenous and iso-lipidic experimental low-FM diets were formulated with enzyme-digested hydrolysed porcine mucosa (EH) at concentrations of 0 g/kg (EH0, controls), 30 g/kg (EH3), 60 g/kg (EH6), 90 g/kg (EH9) and 120 g/kg (EH12). Juvenile hybrid groupers (n = 450; initial body weight 7.50 ± 0.02 g) were randomly divided into 15 tanks and fed the experimental diets twice daily for 56 days. The weight gain rate, specific growth rate, protein efficiency rate, feed conversion rate and fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
(97 reference statements)
2
4
0
Order By: Relevance
“…In the present study, no significant differences were found in CF, which is supported by the results obtained by Gao et al [48] and Yang et al [61] when they replaced FM with HPM equivalents in diets for carp and hybrid grouper, respectively. The VSI did not show significant differences either, such as in the study by Ridwanudin et al [62], in diets with dietary NT for rainbow trout, unlike Gao et al [48] and Yang et al [61], who did find that the VSI increased significantly in diets that included HPM equivalents compared with the control group. The HSI presented significant differences, where diets N250, P1, and P2 showed values close to the control diet.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, no significant differences were found in CF, which is supported by the results obtained by Gao et al [48] and Yang et al [61] when they replaced FM with HPM equivalents in diets for carp and hybrid grouper, respectively. The VSI did not show significant differences either, such as in the study by Ridwanudin et al [62], in diets with dietary NT for rainbow trout, unlike Gao et al [48] and Yang et al [61], who did find that the VSI increased significantly in diets that included HPM equivalents compared with the control group. The HSI presented significant differences, where diets N250, P1, and P2 showed values close to the control diet.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the SL and ML, these did not present significant differences, resulting in the smallest thickness in both parameters, obtained in the group of the control diet (AA0) with respect to the other diets. In contrast, the results obtained by Yang et al [61] in hybrid grouper feed indicate that the muscle thickness of PI in control group was significantly higher than in the groups with HPM equivalents addition. Normally, SL is the layer located on the outside of the ML, it is formed by a secretory epithelial layer (mesothelium) and another layer of connective tissue that supplies nutrients to the epithelium through blood vessels [79].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It was reported that chicken intestinal hydrolysates could replace 50% of fishmeal and did not significantly affect the growth performance and intestinal immunity of common carp, Cyprinus carpio [18]. Enzymedigested hydrolyzed porcine mucosa was used to substitute for 9.1% fishmeal without negative effects on growth as well as the digestive and absorptive functions of the intestines in the hybrid grouper Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂ [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that fish have the ability to differ the taste of chemical substances (Kasumyan & Mouromtsev, 2020), therefore it is important to observe the taste preferences of these animals so that, increasingly, studies are carried out to include foods/ingredients that can act as growth producers and improve the health of the animal, since more attractive and palatable foods can increase the consumption of the offered diets (Al-Souti et al, 2019;Jingting et al, 2020;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%